Strategy of teacher in Improving the Learning Outcomes of Public Junior High School Students - Sihotang, Din Oloan; Sitinjak, Ricardo (Universitas Pahlawan Tuanku Tambusai, 2024)
One of the factors influencing learning outcomes is the ability of teachers to implement teaching strategies effectively. A monotonous teaching process can lead to decreased student motivation and lower learning outcomes. This study aims to investigate the teaching strategies used by Catholic Education teachers to enhance student learning outcomes at SMP Negeri 2 Namorambe. The research adopts a qualitative approach, where data obtained is analyzed through data reduction, data presentation, and drawing conclusions. The findings reveal that teachers utilize various strategies to improve student learning outcomes, such as employing instructional models involving syntax, principles of social system response, supportive systems, and instructional impact. Following the implementation of these strategies, student learning outcomes in Catholic Education subjects show improvement across cognitive, affective, and psychomotor aspects. The effective classroom management skills of teachers also positively impact student learning outcomes. Therefore, the participation and support of the school community, particularly the school principal, are crucial in facilitating the enhancement of teaching quality and mastery of instructional models among teachers